Use of Concrete Object Media to Improve Mathematics Learning Outcomes of Value and Equivalence of Currency Fractions - Emila Sholikhati (Universitas Sebelas Maret, 2020)
This study aims to determine the increase in learning outcomes in online learning through concrete object learning media. This research is a classroom action research with the research subjects of grade II students of SD Margadana 8 Tegal City as many as 28 people. This research was conducted in 3 cycles, each cycle of 2 meetings. Each meeting consists of 4 stages, namely planning, implementing, observing and reflecting. The implementation of the research stages is slightly different from classroom learning because learning is carried out separately or students are in their respective homes. Based on the results of the research, in the first cycle, it was obtained an average of 65.36 classical student learning outcomes with 54% student completeness success, and in the second cycle it was obtained an average student learning outcomes classically 77 with completeness success increased to 79% and still being below the success indicator. In the third cycle, it was obtained the classical average of student learning outcomes 87 with the success of student completeness increased to 96% in this case it was more than the 85% achievement indicator. So from cycle I, cycle II and cycle III there is an increase in student learning outcomes. So, in this study it can be concluded that using concrete object media can improve student learning outcomes in online learning in Mathematics, the subject of value and currency denomination equivalence.